Cover Picture: Macromol. React. Eng. 12/2014. Issue 12 (December 2014) - Pladis, Prokopios; Karidi, Konstantina; Mantourlias, Theofanis; Kiparissides, Costas
<x xml:space="preserve">Abstract</x> Cover: A theoretical and experimental investigation of the ring‐opening polymerization of L, L‐lactide in the presence of Sn(Oct)2 for the production of high molecular weight PLLA at melt conditions is described. Further details can be found in the article by C. Kiparissides and co‐workers on page 813. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>